2017
DOI: 10.18632/oncotarget.23125
|View full text |Cite
|
Sign up to set email alerts
|

CD44 drives aggressiveness and chemoresistance of a metastatic human osteosarcoma xenograft model

Abstract: BackgroundOsteosarcoma is the most common primary malignant bone tumor with a 5 year survival rate of up to 70%. However, patients with metastatic disease have still a very poor prognosis. Osteosarcoma metastasis models are essential to develop novel treatment strategies for advanced disease.MethodsBased on a serial transplantation approach, we have established a U-2 OS osteosarcoma xenograft model with increased metastatic potential and compared it to other metastatic osteosarcoma models from international so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
4
19
0
1
Order By: Relevance
“…In meningioma and gastric cancer, high CD44 expression was correlated with tumor cell proliferation and invasion [45,46]. Previous study showed that siRNA-mediated knockdown of CD44 significantly attenuates migration, invasion and viability of osteosarcoma cells [37]. We have similar findings with the application of CD44 sgRNA CRISPR/Cas9.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In meningioma and gastric cancer, high CD44 expression was correlated with tumor cell proliferation and invasion [45,46]. Previous study showed that siRNA-mediated knockdown of CD44 significantly attenuates migration, invasion and viability of osteosarcoma cells [37]. We have similar findings with the application of CD44 sgRNA CRISPR/Cas9.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have noted that knockdown CD44 by shRNA in osteosarcoma cell lines (U2-OS, KHOS) could efficiently decrease the osteosarcoma potential to metastasis [37]. However, the effect of knocking out targeted gene by RNAi-based techniques is neither permanent nor complete [9].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was reported that CD44, a transmembrane glycoprotein, is aberrantly expressed in several cancers and regulates cancer cell migration, invasion, and metastasis by interacting with extracellular ligands [35]. It is also considered an important stem cell marker and is responsible for resistance of tumor cells to drugs [20,[36][37][38]. Transmembrane CD44 is a non-tyrosine receptor and transmits its signals through the oncogenic protein Src and activation of down-stream effector molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The action of CD44 in murine osteosarcoma appears to parallel osteosarcoma development in humans. CD44 is upregulated in metastatic subclones of human osteosarcoma and promotes lung metastasis formation in an allograft assay 33‐35 …”
Section: Discussionmentioning
confidence: 99%